2013
DOI: 10.1089/scd.2012.0244
|View full text |Cite
|
Sign up to set email alerts
|

Enrichment and Characterization of Human Dermal Stem/Progenitor Cells by Intracellular Granularity

Abstract: Adult stem cells from the dermis would be an attractive cell source for therapeutic purposes as well as studying the process of skin aging. Several studies have reported that human dermal stem/progenitor cells (hDSPCs) with multipotent properties exist within the dermis of adult human skin. However, these cells have not been well characterized, because methods for their isolation or enrichment have not yet been optimized. In the present study, we enriched high side scatter (SSC high )-hDSPCs from normal human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 61 publications
0
7
0
2
Order By: Relevance
“…It is also difficult to obtain adult stem cells because of their limited quantities in the tissue. According to some previous literatures, they are considered to be composed of 0.01% to 0.001% of the total cell number (Hill et al, 2012;Rendl et al, 2005;Riekstina et al, 2009;Shim et al, 2013;Wegner and Stolt, 2005;Wu et al, 2010). We found that hDSPCs in small quantity gradually lose pluripotency and the ability to proliferate once they are grown over long-term culture.…”
Section: Introductionmentioning
confidence: 80%
“…It is also difficult to obtain adult stem cells because of their limited quantities in the tissue. According to some previous literatures, they are considered to be composed of 0.01% to 0.001% of the total cell number (Hill et al, 2012;Rendl et al, 2005;Riekstina et al, 2009;Shim et al, 2013;Wegner and Stolt, 2005;Wu et al, 2010). We found that hDSPCs in small quantity gradually lose pluripotency and the ability to proliferate once they are grown over long-term culture.…”
Section: Introductionmentioning
confidence: 80%
“…Unexpectedly, corin expression was detected in the dermal papilla of hair follicles in mice and humans [54, 55]. The biological significance of corin in the skin is not completely understood.…”
Section: Mouse Models Of Corin Deficiencymentioning
confidence: 99%
“…The isolation of skinderived precursor cells with neurogenic properties has been previously reported from human dermis [13][14][15] and hair follicles [16] as have the isolation and partial purification of adult multipotent stem cells from human and murine epidermis [17,18]. For instance, Fujimori et al reported the isolation of human epidermal stem/progenitor cells by means of gravity-assisted cell sorting [17].…”
mentioning
confidence: 99%